Asymptotic expansions for some semiparametric program evaluation estimators - Hidehiko Ichimura; Oliver Linton (Centre for Microdata Methods and Practice (cemmap), 2001)
We investigate the performance of a class of semiparametric estimators of the treatment effect via asymptotic expansions. We derive approximations to the first two moments of the estimator that are valid to 'second order'. We use these approximations to define a method of bandwidth selection. We also propose a degrees of freedom like bias correction that improves the second order properties of the estimator but without requiring estimation of higher order derivatives of the unknown propensity score. We provide some numerical calibrations of the results.
Keywords: C14; 330